Uvelar Sounds for the advanced scholars - Ahmed Abidl Kareem Yassen Al Azawi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
This research sheds light on the content that many linguists made big efforts to limit it in language and terminology. It is about Uvelar Sounds , a phonological study . Here , we try to study these letters and to give them a precise description through knowing their place of articulation. Then we will be able to order their places in distal pharynx, jaws, tongue and lips. After that we can limit their phonetic qualities such as voiced , voiceless intensity, and softness. In this research we follow a clear phonological approach In the guidance of the words of the Arabs contained in the rich critical heritage. From here our concern was to know the four letters and their importance and show them according to their sound.